Integrating Automatic Arm Lifting Systems to Minimize Wire Broom Damage in Electric Road Sweepers - Sakarinto, Wikan; Maula, Mohamad Izzur; Lutanto, Agus; Falah, Fajrul; Prihtiantoro, Dedhy; Djati, Isworo; Sugiyanto, Sugiyanto (Jurnal Rekayasa Mesin, 2024)
Electric road sweepers often face damage to wire broom components due to manual operation errors, particularly when navigating obstacles like speed bumps. To mitigate this, an automatic arm lifting system using proximity sensors was developed to enhance efficiency and extend broom lifespan. This study focused on designing the wiring, determining optimal sensor detection distances, and assessing sensor angle inclinations for an electric road sweeper prototype. Functional testing determined that Sensor A should be placed 60 cm from the wire broom with a tilt angle of 42.2Ëš, a distance of 2936 mm to the ground, and 2800 mm to the object for lifting commands. For Sensor B, the lowering command requires a tilt angle of 49.4Ëš, a distance of 20 cm from the wire broom, 2692 mm to the ground, and 2200 mm to the object. These settings ensure the system effectively lifts the sweeper arm over obstacles, enhancing both efficiency and durability. The findings demonstrate the potential for advanced sensor technology to improve urban cleaning equipment and support sustainable city maintenance practices.